The Relationship between Income Inequality, Poverty and Globalisation - Almas Heshmati (Institute for the Study of Labor (IZA), 2004)
This paper introduces two composite indices of globalisation. The first is based on the Kearney/Foreign Policy magazine and the second is obtained from principal component analysis. They indicate the level of globalisation and show how globalisation has developed over time for different countries. The indices are composed of four components: economic integration, personal contact, technology and political engagement, each generated from a number of indicators. A breakdown of the index into major components provides possibilities to identify sources of globalisation at the country level and associate it with economic policy measures. The empirical results show that a low rank in the globalisation process is due to political and personal factors with limited possibility for the developing countries to affect. The high ranked developed countries share similar patterns in distribution of various components. The indices were also used in a regression analysis to study the causal relationships between income inequality, poverty and globalisation. Inequality is negatively correlated to globalisation, and globalisation reduces poverty.
Keywords: F15; D63; C23; O57; 330; globalisation; income inequality; poverty; indices; principal component; Einkommensverteilung; Armut; Globalisierung; Wirtschaftsindikator; Schätzung; Welt; Entwicklungsländer